Organozinc hydrazides and their derivatives: synthesis, structural diversity and applications. (24th May 2021) - Jana, Surajit; Saha, Rajat
Abstract : This review highlights the synthetic aspects, structural diversity and possible applications of organozinc hydrazides and their derivatives. Abstract : Organozinc hydrazides have gained considerable interest in current research for their significant applications as single source molecular precursors in chemical science as well as their versatile structural diversity. Various hydrazide derivatives are normally prepared from a 'one-pot' synthesis protocol by reacting dialkylzinc and hydrazine in the presence of secondary ligands at an appropriate ratio, and the reaction proceeds via successful replacement of one or more hydrazide units by secondary ligands through alkane elimination. Due to the polydentate binding nature of the N–N moiety of the hydrazine ligand, these organozinc hydrazides adopt a great variety of structures such as four-membered heterocycles, polycyclic frameworks and cages. The hydrogen storage properties of selected hydrazides and their derivatives are also discussed in this review.